IMPLEMENTATION OF JOHN HOLLAND'S CAREER THEORY IN GUIDANCE AND COUNSELING - Putri, Ramtia Darma; Sari, Syska Purnama (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2018)
Unemployment cases should be a reference for guidance and counseling teachers (hereinafter referred to as BK) to be able to participate in efforts to reduce unemployment by providing BK services in the career field. BK offers a container in the form of various materials in order to fulfill its function. One form of implementing John Holland's career theory itself can be applied in career guidance with classical information services. In its application, this theory suggests the selection of one's work is inseparable from his personality. Someone expresses himself, his interests and values ??through his choice of work. In addition, this theory also recognizes RIASEC personality types that are used as students' grip in determining their future careers.